Anisotropic carrier mobility in two-dimensional materials with tilted Dirac cones: theory and application. Issue 35 (15th August 2017) - Cheng, Ting; Lang, Haifeng; Li, Zhenzhu; Liu, Zhongfan; Liu, Zhirong
Abstract : An analytical formula for the carrier mobility in semimetals with tilted Dirac cones was obtained, and applied to 8B- Pmmn borophene and 2BH- Pmmn borophane. Abstract : We have theoretically investigated the intrinsic carrier mobility in semimetals with tilted Dirac cones under both longitudinal and transverse acoustic phonon scattering. An analytical formula for the carrier mobility was obtained. It shows that tilting significantly reduces the mobility. The theory was then applied to 8B- Pmmn borophene and borophane (fully hydrogenated borophene), both of which have tilted Dirac cones. The predicted carrier mobilities in 8B- Pmmn borophene at room temperature are 14.8 × 10 5 and 28.4 × 10 5 cm 2 V −1 s −1 along the x and y directions, respectively, both of which are higher than that in graphene. For borophane, despite its superhigh Fermi velocity, the carrier mobility is lower than that in 8B- Pmmn owing to its smaller elastic constant under shear strain.